Electric and lighting energy audit: a case study of selective commercial buildings in Dhaka - Rayhana, Rakiba; Khan, Asif Uddin; Hassan, Tahsin; Datta, Ratan; Chowdhury, Abdul Hasib (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the IEEE International WIE Conference on Electrical and Computer Engineering, WIECON-ECE 2015; Bangladesh University of Engineering and Technology (BUET) Dhaka; Bangladesh; 19 December 2015 through 20 December 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/WIECON-ECE.2015.7443923